Pediatric Craniofacial Ballistic Injuries - Teal, Lindsey; Birgfeld, Craig B.; Susarla, Srinivas M. (Seminars in Plastic Surgery, 2025)
Pediatric ballistic injuries are a public health crisis in the United States. Younger children are more likely to sustain craniofacial injuries, which are associated with higher mortality rates. An understanding of the timeline of craniofacial development and the variation in pediatric facial proportions over time is important to guide further treatment of these patients. Management of these patients includes initial stabilization according to the Advanced Trauma Life Support protocol followed by management of time-sensitive injuries. Ballistic injuries often result in soft tissue and bone defects, requiring fixation and coverage. As children experience faster rates of bone healing, fixation should be done promptly. Soft tissue coverage is dependent on the size of the defect; whereas smaller wounds can be closed with primary closure or local tissue rearrangement, larger wounds may require free tissue transfer.
Keywords: pediatric ballistic injuries; pediatric craniofacial fractures; facial fractures; craniofacial development